Odpowiedzi

2009-11-16T17:59:52+01:00
A) 7(x² - 3x - 2) - 3(x² - 6x +1) = 7x²-21x-14-3x²+18x-3 = 4x²-3x-17
4*(-0,2)²-3*(-0,2)-17 = 1,6+0,6-17 = -14,8

b) x(3xy - y) - y(x² - xy + x) = 3x²y-xy-x²y+xy²-xy = 2x²y+xy²-2xy
2*(-1)²*⅕+(-1)*(⅕)²-2*(-1)*⅕ = 2*1*⅕+(-1)*1/25+⅖ = ⅖-1/25+⅖ = 10/25-1/25+10/25 = 19/25 = 0,76
2009-11-16T18:06:45+01:00
A) 7[(-0,2)² - 3(-0,2) - 2] - 3[(-0,2)² - 6(-0,2) +1]= 7(0,04 + 0,6 - 2) - 3(0,04 + 1,2 +1) = 7(-1,36) - 3(2,24) = -9,52 - 6,72 = - 16,24

b) -1[3(-1)⅕ - ⅕] -⅕[(-1)² - (-1)⅕ + (-1)] = -1 (-3/4 - ⅕) - ⅕(1 + ⅕ - 1) = -1(-4/5) - ⅕(⅕) = 4/5 - 1/25 = 20/25 - 1/25 = 19/25